2019
DOI: 10.1007/s10021-019-00356-y
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhiza, Friend or Foe?

Abstract: Many ecology textbooks present the interaction between mycorrhizal fungi and their host plants as the archetype of symbiosis or mutualism. However, mycorrhiza drains carbon directly from the plant and also competes with the plant for soil inorganic nitrogen. We developed hypotheses based on a simple model to qualitatively investigate when, in a nitrogen-limited system, the fungal partner returns sufficient extra nitrogen to compensate for the amount of carbon allocated to it by the plant. We showed when the my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Ectomycorrhizal fungi may also have beneficial interactions with plants. Many tree species form symbiotic associations with ectomycorrhizal fungi which are known to enhance the uptake of nutrients by plants ( Kieliszewska-Rokicka, 1999;Ågren et al, 2019) or which provide protection by alleviating them of heavy metal toxicity (Luo et al, 2014;Egerton-Warburton, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Ectomycorrhizal fungi may also have beneficial interactions with plants. Many tree species form symbiotic associations with ectomycorrhizal fungi which are known to enhance the uptake of nutrients by plants ( Kieliszewska-Rokicka, 1999;Ågren et al, 2019) or which provide protection by alleviating them of heavy metal toxicity (Luo et al, 2014;Egerton-Warburton, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of leaf P levels, a growing trend was observed over time, but without significant differences between treatments, which may reflect the establishment of symbiotic associations between plants and native microorganisms. It should be noted that the olive tree is the main crop in the region and beneficial microorganisms, particularly ectomycorrhizal and AM fungi, tend to be ubiquitous in nature and establish symbiotic associations with most plant species [13,17,50]. P is the most common nutrient from which plants benefit when these associations are established [20,23,51], particularly in acidic soils, where it is expected to be poorly available to plants [47,52].…”
Section: Discussionmentioning
confidence: 99%
“…Fungal growth type and foraging strategy may, for example, be simple parameters for ECM fungal classification, as both relate to the C demand of the fungus and its ability to find and source soil nutrients (Agerer, 2001;Clemmensen et al, 2014). Others have suggested that fungal C cost per unit N provided may be useful in characterizing the association (Corrêa et al, 2008;Agren et al, 2019); however, this is a complicated measure that may change dramatically based on external situations, or even over the lifetime of the mycorrhizal association (Nehls et al, 2016).…”
Section: Future Research Directionsmentioning
confidence: 99%